Peranan Aplikasi Tiktok Sebagai Konten Islam Terhadap Pemahaman Mahasiswa Komunikasi Penyiaran Islam Universitas Muhammadiyah Palembang Angkatan 2021 - Fathul Khorib; Muhammad Zainudin Naawi; Ayu Munawaroh (Jurnal Intelek Insan Cendikia, 2025)
The Tiktok application is an application that is popular with various groups, becoming one of the most popular applications in today's era. Islamic content is now widely disseminated through Tiktok. So the purpose of this study was to determine the role of the Tiktok application as Islamic content in providing understanding to students of Islamic Communication and Broadcasting class of 2021, Muhammadiyah University of Palembang. This study uses a qualitative research method, with data collection techniques, observation, interviews and documentation. Data analysis starting from data reduction, data presentation, and drawing conclusions. The results of this study indicate that the role of Tiktok as Islamic content through short, interesting and clearly conveyed Islamic content makes the role of the Tiktok application very effective and efficient in providing students with an understanding of the Islam they receive.